Prevalence of Transfusion Transmissible Infections In Blood Donors - Hoque, Md Monirul; Saha, Debashish; Khan, Arif Ahmed; Tarek, Monwar; Shourov, Md Mehedhi Hasan (Bangladesh Journal of Medical Microbiology, 2018)
Background: Blood transfusion is a significant life-saving intervention in the present era of patient management system. As the blood and blood products are a potential source of infection and the necessity of transfusion is increasing day by day, transfusion transmissible infections (TTIs) have become a major threat to ensure safe transfusion. Objectives: The aim of this study was to assess the prevalence of some common and serious TTIs among blood donors as well as evaluate the pattern of seroprevalence in accordance with few other characteristics. Methods: It was a cross sectional study which was conducted at the Department of Transfusion Medicine of Armed Forces Institute of Pathology (AFIP), Dhaka Cantonment from January 2015 to June 2017. Donors were selected very carefully according to criteria of National Guidelines of Bangladesh Government and by using a detailed questionnaire. They were screened properly for HBV, HCV, HIV, Malaria and Syphilis. All positive cases were confirmed again by using more sensitive and specific tests. We analyzed the data as percentage and comparison. Results: A total of 32,625 donors were screened. Among them 28,775 were male and 3850 female. Total 135 were found reactive in the screening assays and among them no one was reactive in more than one assays. The prevalence of HBV and HCV in our study population was 0.38% and 0.03% respectively. It was found that percentage of HBV and HCV seropositivity was more among civilian donors. There was no positive case of Malaria, Syphilis and HIV. The number of seropositive cases were found to be decreased gradually in consecutive years. The study also revealed that both HBsAg and Anti-HCV positive cases were more prevalent amongyoung donors. Conclusion: Our study revealed that a significant number of donors were positive for TTIs who might be a potential source of transfusion related infections. It justifies the necessity of stringent screening of blood donors to prevent the transfusion transmissible infections. Bangladesh J Med Microbiol 2018; 12 (1): 20-23